Giant Rashba‐Type Spin Splitting in Ferroelectric GeTe(111). Issue 3 (24th November 2015) - Liebmann, Marcus; Rinaldi, Christian; Di Sante, Domenico; Kellner, Jens; Pauly, Christian; Wang, Rui Ning; Boschker, Jos Emiel; Giussani, Alessandro; Bertoli, Stefano; Cantoni, Matteo; Baldrati, Lorenzo; Asa, Marco; et al.
Abstract : Photoelectron spectroscopy in combination with piezoforce microscopy reveals that the helicity of Rashba bands is coupled to the nonvolatile ferroelectric polarization of GeTe(111). A novel surface Rashba band is found and fingerprints of a bulk Rashba band are identified by comparison with density functional theory calculations.